Union and Employer Confederation Views on Current Labour Relations in 21 Industrialized Nations - Peterson, Richard; Sargent, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1997)
This study reports the results of a cross-sectional mail survey sent to top officials of union and employer confederations in twenty-one industrialized market economics in Western Europe, North America, and Japan. The results regarding their assessment of the current labour relations situation in their own country show some significant differences related to employer vs. Union side and by economic groupings (EEU, EFTA, and other). We conclude that the relatively stable labour-management relationships during the 1960s and 1970s has apparently given way to greater divergence among the major industrial nations in recent years.